Eksplorasi Perilaku Peran Ekstra dan Komitmen Karyawan terhadap Tingkat Kebanggaan Organisasi di PT INKA (Persero) - Anugrah, Silvy Aprilia Citra; Fiernaningsih, Nilawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Extra-role behavior and employee commitment are important factors in enhancing employees' sense of pride in their organization. This study aims to analyze the level of employee pride in the organization in terms of extra-role behavior and commitment among employees in the Talent Management and Training Department of PT INKA (Persero). Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation methods. The results of the study indicate that some employees have not yet had the opportunity to engage in extra-role behavior, and employee commitment is generally driven by personal factors rather than internal organizational factors. These findings are expected to provide insights to enhance employees' sense of pride in the organization through the perspectives of extra-role behavior and employee commitment.